Statistical motor unit number estimation: From theory to practice - Lomen-Hoerth, Catherine; Slawnych, Michael P. (Muscle & nerve, 2003)
Statistical motor unit number estimation (MUNE) is one of several experimental techniques used to estimate the number of lower motor neurons innervating a given muscle. All are fairly reproducible and have been applied successfully in monitoring neurogenic disease progression. Quantitating the number of lower motor neurons is important, since the compound muscle action potential (CMAP) and strength may not change as rapidly over time due to the confounding effect of reinnervation. MUNE techniques differ in the way they obtain samples of surface‐recorded motor unit potentials (SMUP). Statistical MUNE is based on Poisson statistics, uses surface stimulation, and is useful in testing distal, superficial nerves. This review focuses on the theory behind the development of the technique, critiques the publications resulting from applying the technique in control and disease subjects, and discusses the future developments needed for clinical utility. Muscle Nerve 28: 263–272, 2003